KOSAKATA BARU PADA PEMBERITAAN TENTANG PANDEMI COVID-19 DAN PEMANFATAANNYA DALAM PEMBELAJARAN BAHASA INDONESIA DI SMP - Annisa, Fajar Nur; SUMARWATI, SUMARWATI SUMARWATI; ROHMADI, MUHAMMAD (University of Brawijaya, 2022)
This study aims to describe and explain (1) the new linguistic forms used by Kompas daily during the Covid-19 pandemic, (2) the process of forming a new language used by Kompas daily during the Covid-19 pandemic (3) the use of analysis of forms and processes for the formation of new languages used Kompas daily during the Covid-19 pandemic as Indonesian language teaching materials in Junior High Schools. This study was a qualitative research with a morphological process content analysis approach. The sampling technique used is purposive sampling technique. The data collection techniques in this study used two ways, namely document analysis and in-depth interviews. Document content analysis is obtained by observing and taking notes. Test the validity of the data in this study using method triangulation and source triangulation. The data analysis technique used is flow model ofÂ analysis. The results show that the new vocabulary found in the Kompas daily newspaper amounted to 144 data which were classified into five forms. The abbreviations consisting of 24.31 percent and single words 23.61 percent with a difference of 0.7 percent. Then followed by acronyms 17.36 percent, compound words 12.50 percent, and phrases 22.22 percent. The collection of new vocabulary during the Covid-19 pandemic in the Kompas daily newspaper can be used as teaching material for news texts for class VIII SMP. This result are consistent with basic competencies 3.2 and 4.2 related to linguistic structure and presentation patterns in the form of news texts.